Spatial Patterns of Particles and Plankton in the Warming Arctic Fjord (Isfjorden, West Spitsbergen) in Seven Consecutive Mid-Summers (2013–2019) - Szeligowska, Marlena; Trudnowska, Emilia; Boehnke, Rafał; Dąbrowska, Anna Maria; Wiktor, Józef Maria; Sagan, Sławomir; Błachowiak-Samołyk, Katarzyna (Frontiers in Marine Science, 2020)
The restructuring of planktonic communities towards an increasing share of small individuals is not only expected, but also already observed consequence of warming in the rapidly changing Arctic. Here we demonstrate a simultaneous study on the nano-, micro- and mesoplankton (divided into small and large), and corresponding size fractions of particles along a hydrographical gradient in the Isfjorden – the largest Spitsbergen fjord system. The sampling was performed in 7 following summers (2013-2019) from the main basin under the influence of Atlantic Waters (ISA station), up to Billefjorden – the innermost part affected by meltwaters from Nordenskiöldbreen (BAB station). Our objective was to elucidate the composition and spatial patterns in distribution of plankton and particles (P&P) under various hydrographical regimes. Combining two laser-based measurements (LOPC and LISST) with standard plankton analysis allowed us to conclude that vertical hydrographical stratification and eddy activity were forcing either layered or patchy distribution of P&P. The concentrations of P&P measured by LISST (nano- and micro-) were lower than the abundance of the corresponding size fractions of protists, but they did not differ significantly among the stations due to different origin of P&P. Nevertheless, the decreasing trend in the abundance of both investigated mesoplankton fractions could be observed between the ISA and BAB stations, whereas the opposite tendency was noted for P&P. Moreover, the abundance of mesoplankton was equal to the concentrations of the corresponding size fractions of P&P at the ISA station and much lower than the LOPC counts at the BAB station, which points towards notable amount of marine aggregates in the glacial bay. Even if some observations alluded to P&P susceptibility to the local processes, the inter-annual variability in P&P distribution surpassed the differences between the sampling stations. It suggests that both the large-scale processes (i.e. intensified inflow of Atlantic Waters) and natural seasonal changes associated with subtle differences in sampling timing had a stronger influence on investigated plankton than local factors. This pioneering study, which links traditional and advanced methods, clearly demonstrated that such approach is convenient for tracking small-scale spatial patterns and inter-annual variability of P&P in the Arctic pelagial.